Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

“What is a House without Food?”: Mozambique’s Coal Mining Boom and Resettlements (Human Rights Watch, 2013)
“What is a House without Food?” Mozambique’s Coal Mining Boom and Resettlements
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Peril dos dados básicos das cidades de Moçambique. Edição preliminar. - Ventura, Albert Gerard; Pazero, Renata; Hoelich, Sara; Bennaton, Alessa; Llop, Josep Maria (ASF - Catalunya/Secretariado Mundial CGLU / Cátedra UNESCO - Red CIMES, 2013)
O projeto que tem previsto uma duração de 28 meses e foi iniciado em janeiro de 2013, prevê a melhoria da capacidade de gestão do desenvolvimento de oito municípios em Moçambique e seis no Brasil, assim como de duas associações de autoridades locais (Associação Nacional de Municípios de Moçambique - ANAMM - e Frente Nacional de Prefeitos do Brasil -FNP), mediante ações de intercâmbio de boas práticas, capacitação institucional e articulação em rede das AL. O projeto é coordenado por Cidades e Governos Locais Unidos (CGLU), juntamente com Arquitectos sem Fronteiras (ASF) e Cátedra UNESCO / Rede-CIMES. Conecta-se com os processos de descentralização e fortalecimento dos governos locais. No Brasil, cuja trajetória é mais larga, estes vêm marcados principalmente pelas políticas do Ministério das Cidades e do Estatuto da Cidade (2001), que desenvolveu o Plano Diretor como a peça central do desenvolvimento deinido na Constituição de 1988, além de outros instrumentos de gestão urbana. De um modo similar mais recente, em Moçambique se está desenvolvendo uma política de descentralização da gestão urbana municipal. Usando instrumentos similares de planejamento, deinidos na Lei de Ordenamento do Território, a Política Nacional de Habitação reconhece a acesso à habitação adequada como um direito e vetor de inclusão social e deine as ferramentas para a sua implementação. No entanto, estas políticas ainda não tem uma dotação orçamentária deinida. A ação propõe os seguintes objetivos especíicos: 1. Melhorar as capacidades institucionais de gestão do desenvolvimento das Autoridades Locais (AL), consolidando-as como agentes de desenvolvimento em nível local e como atores de desenvolvimento em nível nacional e internacional no âmbito da cooperação descentralizada Sul-Sul. 2. Consolidar a articulação em rede de Autoridades Locais em Associações de Autoridades Locais (AAL), possibilitando a sua projeção como atores em cooperação, a criação de sinergias entre Autoridades Locais e fomentando a sua interação com outros atores descentralizados Concretamente, o projeto inclui o desenvolvimento, a adaptação local, a gestão e conhecimento de três ferramentas: o Planejamento Base, o Cadastro Inclusivo e o Plano de Orçamento Participativo / Business Plan mediante a troca de experiências entre as cidades dos dois países.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; south-south cooperation / cooperação sul-sul

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo, Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra

Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Mid-Term Review of the AGIR Programme. Final report. - Kelpin; Johnsen, Vibe; Macuane, José Jaime; Christoplos, Ian; Rothman, Jessica (Decentralised Evaluation, 2013)
This mid-term review report of the ‘Action Programme for Inclusive and Responsible Governance’ (AGIR) in Mozambique was carried out from August 2012 to its completion at the end of October 2012 by a three-member review team fielded by Indevelop. A presentation of the preliminary findings was made on October 24th, 2012 to AGIR intermediaries and AGIR CSO partners. Subsequent to this presentation, the review team was provided with the just-completed 2012 semi-annual report, which was written and submitted jointly by AGIR intermediary organisations. AGIR has duration of five years beginning in 2010 and ending in 2014. Sweden is the only core donor, with Denmark and the Netherlands also providing support to participating INGOs (International Non-Governmental Organisations). The programme works with both national partners and with organisations in the provinces. In an effort to strengthen civil society and civil society organisations within Mozambique, the Swedish Embassy initiated the AGIR programme in 2010. The objective of AGIR is to: Support Mozambican civil society organisations, strengthening their capacity for and impact on improving transparency, accountability, citizen’s participation, access to information, respect for human rights, and gender equality. In line with the Paris Declaration and the Accra Agenda for Action, AGIR is structured to provide “good donor-ship” through support given for CSO ‘core funding’ that is aligned with the “strategic direction of the organisation” and to support and facilitate linkages and knowledge sharing between Mozambican CSOs.2 The main support modality for this capacity strengthening of CSOs is to “work through a limited number of qualified intermediary organisations within the following four clusters of support: i) Participation, social and legal accountability, including monitoring of respect for human rights; ii) Social accountability in management of natural resources and community land rights; iii) Transparency, financial and political accountability; and, iv) Promotion of access to information.”
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

Support to Civil Society Engagement in Policy Dialogue - Ministry of Foreign Affairs of Denmark (Joint Evaluation, 2013)
This evaluation, the ‘Joint Evaluation of Support to Civil Society Engagement in Policy Dialogue’ was initiated by the Donor Group on Civil Society and Aid Effectiveness. Specifically it was commissioned by three Development Partners (DPs), ADC/Austria, Danida/Denmark and Sida/Sweden, which form the Management Group. A larger group of bilateral DPs support the evaluation through their participation as the international Reference Group. The evaluation took place between June 2011 and September 2012. The Evaluation Team was drawn from the consulting firm ITAD Ltd in the UK (lead firm), together with experts from COWI (Denmark) and experts from each of the three countries selected for the fieldwork, Bangladesh, Mozambique and Uganda. The purpose of this evaluation is lesson learning, to help DPs gain a better understanding of how best to support Civil Society Organisations (CSOs) in the area of policy dialogue. The findings will also have direct relevance to the CSOs in the three countries and the wider CSO community, as well as the Governments and local authorities interacting with Civil Society (CS) representatives. The evaluation focuses on: 1. How CSOs engage in policy dialogue and the relevance and effectiveness of their policy work; 2. the enabling environment, that is the enablers and barriers to CSO engagement; and 3. how different DP support strategies may influence CSOs’ ability to engage in policy dialogue, and how best the DPs might support CSO policy dialogue in the future.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; civil society / sociedade civil

Youth Social Exclusion and Lessons from Youth Work: Evidence from literature and surveys - Paolini, Giulia; Brel, Patrice; Vanandruel, Colette (European Commission Education, Audiovisual and Culture Executive Agency (EACEA), 2013)
It is widely recognised that social exclusion produces deep and long-term damage to the living conditions, social and economic participation, emotional life, and health status of young people. It also contributes to the intergenerational transmission of poverty. In turn, insecurity in living standards, political and social isolation, feelings of estrangement and unhealthy lifestyles aggravate pre-existing conditions of social exclusion. This results in a vicious circle where socially excluded young people are in even more danger of suffering from additional material deprivation, social and emotional marginalisation, and health issues, which in turn expose them to more serious risks of exclusion. Almost one out of three young persons between the ages of 18 and 24 is at risk of poverty or social exclusion in the European Union. Youth work can offer opportunities for preventing and remedying this vicious circle. By offering young people targeted support, opportunities for non-formal learning, information on health and wellbeing, and opportunities for positive integration into the local community, youth workers are able to reduce the risks of further social exclusion linked to deteriorating living conditions and unhealthy life styles. The EU Youth Strategy recognises the relevance of youth work to mitigating the effects of social exclusion amongst young people. Reaffirming this concept, the Council Resolution on Youth Work of 2010 invited Member States and the Commission to support the development of youth work at local, regional, national and European level. The relation between youth work and social inclusion also touches upon the priorities established by the 2012 EU Youth Report. A general overview of the fundamental threats to social inclusion experienced by young people can be found in the dedicated chapter of the Youth Report. The benefits coming from youth work to the inclusion of young people, and in particular of those with a migrant background, has been recognised in the Conclusions of the Council of 27 November 2012. To address the risks of exclusion run by many young individuals, the Social Investment Package adopted by the European Commission seeks to improve the situation of young people by tackling childhood disadvantage, improving access to quality education and support services, helping young people develop skills relevant to the labour market, and ensuring work experience and on-the-job training and helping young people find a first good job (European Commission, 2013a). This paper aims at offering evidence about the situation of social exclusion suffered by young people in the European Union, and the positive effects that youth work initiatives produce in fostering their (re)inclusion. Looking at factual information on the main conditions of exclusion is essential to have an accurate understanding of the threats encountered by young people. Available data and research literature illustrate the major reasons behind the marginalisation of young Europeans, and pave the way to the development of effective policy strategies to prevent it.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; youth / juventude